The International Encyclopedia of Biological Anthropology 2018
DOI: 10.1002/9781118584538.ieba0537
|View full text |Cite
|
Sign up to set email alerts
|

Growth in childhood and adolescence

Abstract: The human growth pattern with different developmental stages is a result of evolutionary trade‐offs showing specific features. The prolonged childhood and adolescence with their typical growth spurts is associated with age‐ and sex‐specific development of maturation signs, and changes of body proportions and dimensions. Biological age can be estimated with different methods and helps to classify human growth‐specific biological age stages. These stages include typical body markers, but also sociocultural and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 9 publications
1
33
1
2
Order By: Relevance
“…However, the results of this research also showed that the ES of maturation with the performance of muscle strength in rowers was of a lower magnitude than the ES found in other sports (see Table 5). Our results differ from previous studies, which found relationships between lean mass and advanced maturation regardless of the analyzed sport [19][20][21][22]40,41].…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results of this research also showed that the ES of maturation with the performance of muscle strength in rowers was of a lower magnitude than the ES found in other sports (see Table 5). Our results differ from previous studies, which found relationships between lean mass and advanced maturation regardless of the analyzed sport [19][20][21][22]40,41].…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that the present study also demonstrated that chronological age is not a safe marker of biological age, when observing that the sample used was in the age group between 10 and 12 years old (age: 11.3 ± 0.96) and the maturation stage typical for this age group is the prepubertal [10,22,41]. However, it is known that environmental factors such as nutrition, quality of sleep, physical and cognitive stimuli interact with the puberty process.…”
Section: Discussionmentioning
confidence: 52%
“…Our group has already demonstrated that through linear regression analyses and artificial neural networks, the biological maturation markers of female subjects show about a 50% probability of predicting the neuromotor performance of upper and lower limbs [14], while hormonal markers discriminated a potential 95% chance of predicting upper limb neuromotor performance [14]. The approach highlights that although environmental factors may significantly interfere with hormonal levels (i.e., food, sleep quality, stress levels), there is a significant association between the stages of puberty and hormonal levels in children and teenagers [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropometric variables (i.e., height, limb length, etc.) cannot be modulated by sports training [2,[5][6][7][8][9]. However, these variables influence the "biomechanical levers" of the human body during the production of muscle strength [2,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%